2020
DOI: 10.1186/s13023-020-01496-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel prognostic model for adult patients with Hemophagocytic Lymphohistiocytosis

Abstract: Background: Hemophagocytic Lymphohistiocytosis (HLH) is a type of rare disease with low survival rate. We aimed to develop a model to evaluate the six-month prognosis in adult HLH patients. The data at discharge (will be called as post-treatment) for newly diagnosed adult HLH patients was collected and independent prognostic variables were selected for inclusion in the model. Results: Three laboratory markers were confirmed to be the independent risk factors (ferritin: hazard ratio (HR) 0.101, 95% confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…High ALT and AST/ALT ratio have been found to act as adverse prognostic factors in adult HLH (8,28). Furthermore, hepatic involvement and hepatomegaly reveal poor prognostic indicators and early death predictors in HLH (8,28). In line with these studies, our results illustrated that the radiomic features of spleen and liver presented great prognostic values for adult HLH.…”
Section: Personalized Nomogram Establishment and Validationsupporting
confidence: 85%
See 3 more Smart Citations
“…High ALT and AST/ALT ratio have been found to act as adverse prognostic factors in adult HLH (8,28). Furthermore, hepatic involvement and hepatomegaly reveal poor prognostic indicators and early death predictors in HLH (8,28). In line with these studies, our results illustrated that the radiomic features of spleen and liver presented great prognostic values for adult HLH.…”
Section: Personalized Nomogram Establishment and Validationsupporting
confidence: 85%
“…In addition, the well-known liver enzymes, AST and ALT, are identified as indicators of various diseases including HLH. High ALT and AST/ALT ratio have been found to act as adverse prognostic factors in adult HLH (8,28). Furthermore, hepatic involvement and hepatomegaly reveal poor prognostic indicators and early death predictors in HLH (8,28).…”
Section: Personalized Nomogram Establishment and Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have shown different prognostic factors for adult HLH. Hypofibrinogenemia, thrombocytopenia, hypoalbuminemia, hyperferritinemia, and elevated lactate dehydrogenase levels are significant predictors of inferior survival [ 18 , 19 ]. Regardless of these identified prognostic factors, tumor-associated HLH had a markedly worse outcome, emphasizing the importance of underlying disease control in lymphoma-associated HLH.…”
Section: Discussionmentioning
confidence: 99%